The Relationship of Materialism and Financial Literacy on Students' Financial Management - Novita Arief; Riyanti; Sahrir (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Study This aim For know connection materialism and literacy finance to management finance student. Types of research This use approach study quantitative through analysis regression multiple use SPSS application. Object in study This is students across the city palopo . Deep Sampling​ study This use accidental sampling method with total of 120 respondents . Research result show that that materialism No influential or not significant to management finances for students in Palopo City, this give results that level caution students in Palopo City be careful in use the money so that make student can manage it his finances with OK, more rational or not will behave consumer. For literacy finance  influential positive and significant to management finance, which means the more tall literacy finance so will make management generated finances​ become the more Good. Keyword: Materialism , Literacy Finance , Management Finance